(untitled) (Revista Brasileira Multidisciplinar, 2022)
Wide-shallow beams (WSBs) are structural elements characterized by having a width larger than its depth. They have special application on structures where beams must have the same thickness than the floor due to architectural requirements. Maximum spacing of shear reinforcement legs shall be provided to meet minimum shear reinforcement, restrain the growth of inclined cracking and improve ductility of the beam. As it depends on the effective height, WSBs usually require closer stirrup spacing, leading to high transverse reinforcement ratio. Steel fibers can be used in reinforced concrete beams to increase shear strength and even replace stirrups. However, most studies about the subject does not apply or is only partially related to WSBs. In this study, ten simply-supported WSBs were tested under a four-point loading system to investigate their shear behavior. Beams, with a total depth of 100 mm, width of 150 mm and 650 mm span, were cast with different amounts of steel fibers (0, 25, 35 and 45 kg/m³). Moreover, beam with minimum amount of transverse shear reinforcement were also produced. The main effects of the fibers, even in small amounts, were providing a flexural residual strength to the concrete and increasing the shear strength of the WSBs, delaying the diagonal shear crack development. The behavior of 45 kg/m³ steel fibers WSBs was significantly modified in relation to the beam without shear reinforcement. Most of the analytical models studied showed a good estimate (about 11% higher than the experimental value) of the shear strength of the WSBs analyzed.